Single-Layer Based Algorithms for Solving the Inverse Problem of ECG - Potyagaylo, Danila; Chmelevsky, Mikhail; Kalinin, Alexander (Computing in cardiology, 2019)
Recently, the equivalent single layer (ESL) source model, along with the respective regularization matrix, was introduced for solving the ECG imaging (ECGI) problem with the boundary element method (BEM).In the present work, we extend the proposed formulation by three additional ECGI methods. The first algorithm is based on substitution of the pseudoinverse transfer matrix for the single layer into the alternative BEM equation (ESL-EP). The second extension consists in an iterative update of the two BEM equations, while alternating between the epicardial potentials and their normal derivative. The third solution approach results from weighting the initial ESL solution with ESL-EP. We tested the proposed algorithms on three in silico and twenty clinical cases for ectopic ventricular excitation and quantitatively compared their performance in terms of reconstructed activation times and earliest activation areas, respectively.The methods featured distinct results with the best mean localization accuracy obtained by the initial ESL and the weighted approaches. ESL-EP and the iterative algorithm facilitated correct classification of the excitation onset being endocardial.